(untitled) (University of Khartoum Engineering Journal, 2021)
This paper presents an experimental evaluation of transmission length in hollow core slabs against 18 suggested equations in some codes of practice in addition to some equations from the previous literature. The experimental transmission length was predicted at 95% average mean strain (95% AMS) by measuring changes in strain after wire cutting on the near concrete face using both electric strain gauge and demountable mechanical strain gauges (DEMEC). The ratio between the measured transmission length and the value predicted using codes of practice equations varied from 1.0 to 1.26. On the other hand, the variation was 0.59 to 1.97 for the equations from the previous literature. The experimental results also confirmed the previous findings of non-linear prestress transfer over the transmission zone